2014
DOI: 10.1161/circulationaha.113.005865
|View full text |Cite
|
Sign up to set email alerts
|

Type A Aortic Dissection in Marfan Syndrome

Abstract: Bad Krozingen reviewed their aortic dissection databases including patients operated on between 1987 and 2013. The cumulative case load at both centers was 1324. Of these, a total of 74 patients (Heart Center Freiburg, 42; University of Pennsylvania, 32; Table) with MFS confirmed according to the revised Ghent criteria 8 underwent surgery for Stanford type A aortic dissection. Patients were followed up in the past 25 years at both institutions in MFS clinics in at least 1-year intervals. Background-Data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(24 citation statements)
references
References 24 publications
2
20
1
1
Order By: Relevance
“…The other remaining 54 VSARR (96.4%) were elective aneurysmal aortic root replacements, which could have also contributed favorably to our outcomes. Furthermore, aortic dissection is a known risk factor with regard to reinterventions of the downstream aorta or the aortic root 1820 . In our cohort operations of the aortic arch and descending aorta – including abdominal aorta - were performed in 6 patients, of whom 4 initially presented with aortic dissections (type A or B), which is also in line with previous findings 1921 .…”
Section: Discussionmentioning
confidence: 99%
“…The other remaining 54 VSARR (96.4%) were elective aneurysmal aortic root replacements, which could have also contributed favorably to our outcomes. Furthermore, aortic dissection is a known risk factor with regard to reinterventions of the downstream aorta or the aortic root 1820 . In our cohort operations of the aortic arch and descending aorta – including abdominal aorta - were performed in 6 patients, of whom 4 initially presented with aortic dissections (type A or B), which is also in line with previous findings 1921 .…”
Section: Discussionmentioning
confidence: 99%
“…Dissecting the brachiocephalic arteries, especially the left subclavian is much more technically demanding. A recent study has found that at the time of initial repair for TAAD in MFS, a more aggressive surgical approach seems to be superior to limited repair (29). However, there is scarce data on the long-term outcomes of such extensive repair for TAAD in such patients (19,22,30).…”
Section: Discussionmentioning
confidence: 99%
“…[13] Stanford type A AD originates primarily in the ascending aorta just above the aortic valve. [4] In spite of the substantial advances made in diagnostic imaging methods and surgical techniques for treatment, the mortality of type A AD still averages 25%. [5] Further difficulties in prevention and therapeutic management arise from the fact that the responsible molecular and genetic determinants of type A AD remain largely unidentified.…”
Section: Introductionmentioning
confidence: 99%